2023
DOI: 10.3389/fchem.2023.1119240
|View full text |Cite
|
Sign up to set email alerts
|

The aqueous supramolecular chemistry of crown ethers

Abstract: This mini-review summarizes the seminal exploration of aqueous supramolecular chemistry of crown ether macrocycles. In history, most research of crown ethers were focusing on their supramolecular chemistry in organic phase or in gas phase. In sharp contrast, the recent research evidently reveal that crown ethers are very suitable for studying abroad range of the properties and applications of water interactions, from: high water-solubility, control of Hofmeister series, “structural water”, and supramolecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…与 传 统 的 吸 附 剂 ( 活 性 炭 [27,29,30] 、沸石 [31] 、吸附树脂 [32,33] 、活性铝 [34] )相比, 超分子大环主体具有分子识别和自适应组装等优点, 可用于构筑多种功能材料 [35,36] . 冠醚 [37] 、杯芳烃 [38] 、 葫芦脲 [39] 、环糊精 [40] 、柱芳烃 [41] 以及各种新型大 环 [42] 主体都是被研究得很充分的人工受体, 其空腔或 分子间隙可以选择性地识别特定的客体 [43] . 其由于具 有吸附容量大、速率快和选择性高等优点, 已被广泛 应用于污染物的吸附、分离和检测等领域.…”
Section: 在过去的几十年里 以超分子大环为基础的有机unclassified
“…与 传 统 的 吸 附 剂 ( 活 性 炭 [27,29,30] 、沸石 [31] 、吸附树脂 [32,33] 、活性铝 [34] )相比, 超分子大环主体具有分子识别和自适应组装等优点, 可用于构筑多种功能材料 [35,36] . 冠醚 [37] 、杯芳烃 [38] 、 葫芦脲 [39] 、环糊精 [40] 、柱芳烃 [41] 以及各种新型大 环 [42] 主体都是被研究得很充分的人工受体, 其空腔或 分子间隙可以选择性地识别特定的客体 [43] . 其由于具 有吸附容量大、速率快和选择性高等优点, 已被广泛 应用于污染物的吸附、分离和检测等领域.…”
Section: 在过去的几十年里 以超分子大环为基础的有机unclassified
“…This recognition led to further research and diversification of applications for these supramolecular systems, which have since been employed in a myriad of applications, ranging from separation sciences to the synthesis of molecular machines. 1,7,8 Recent trends in the field have shown a growing interest in leveraging supramolecular-based ligands for the selective separation of critical materials, underscoring their potential in addressing contemporary material challenges. 9,10 Ion-polyether host-guest interactions occur non-covalently through ion-dipole supramolecular interactions, where the selectivity of ion binding correlates with host cavity size, composition, and ion radius (r).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many efforts have been devoted to construct crown ether-based molecular rotors. The rotational motion of the rotors results in the phase transition to emergence of ferroicity, in which notable advancements have been made based on 18-crown-6. , For instance, Zhu et al synthesized supramolecules by combining 18-crown-6 with metal halogen octahedra and alkali metals, yielding materials with superior photoelectric properties . At the same time, Xiong et al reported the construction of multiaxis ferroelectrics with 18-crown-6 and oxonium tetrachloride-gallium­(III), and they found that oxygen ions in 18-crown-6 could induce ferroelectricity and further increase T c .…”
Section: Introductionmentioning
confidence: 99%